Age-Related Changes in the Cochlea and Vestibule: Shared Patterns and Processes - Paplou, Vasiliki; Schubert, Nick M. A.; Pyott, Sonja J. (Frontiers in Neuroscience, 2021)
Both age-related hearing loss (ARHL) and age-related loss in vestibular function (ARVL) are prevalent conditions with deleterious consequences on the health and quality of life. Age-related changes in the inner ear are key contributors to both conditions. The auditory and vestibular systems rely on a shared sensory organ – the inner ear – and, like other sensory organs, the inner ear is susceptible to the effects of aging. Despite involvement of the same sensory structure, ARHL and ARVL are often considered separately. Insight essential for the development of improved diagnostics and treatments for both ARHL and ARVL can be gained by careful examination of their shared and unique pathophysiology in the auditory and vestibular end organs of the inner ear. To this end, this review begins by comparing the prevalence patterns of ARHL and ARVL. Next, the normal and age-related changes in the structure and function of the auditory and vestibular end organs are compared. Then, the contributions of various molecular mechanisms, notably inflammaging, oxidative stress, and genetic factors, are evaluated as possible common culprits that interrelate pathophysiology in the cochlea and vestibular end organs as part of ARHL and ARVL. A careful comparison of these changes reveals that the patterns of pathophysiology show similarities but also differences both between the cochlea and vestibular end organs and among the vestibular end organs. Future progress will depend on the development and application of new research strategies and the integrated investigation of ARHL and ARVL using both clinical and animal models.